Asymptotic behavior of solutions of pulse systems with small parameter and markov switchings. I. Uniform boundedness of solutions - Sverdan, M. L.; Tsar’kov, E. F.; Yasinsky, V. K. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We consider pulse systems with Markov switchings. We study the problems of uniform boundedness of solutions of these systems and the stability of the systems with respect to the limit equation.